Association of C-Reactive Protein (CRP) with Bipolar Disorder & Gender - Tehmina Tariq, Amna Noor, Shama Akram, Muhammad Ahmad Khan, Nabeel Ibad, Faraha Tariq, Muhammad Fahim-Ul-Haq, Samiah Shahid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Bipolar disorder (BD) is a mental disorder with mood swings that fluctuate between mania, hypomania, and depression. C-reactive protein (CRP) levels in bipolar patients have been studied across the globe, but the results are variable. A very limited research has been conducted in this area in Pakistan. Therefore, the goal of the current investigation was to evaluate CRP in bipolar illness. Moreover any link between CRP and gender was also investigated. Materials and methods: In this cross-sectional study, 112 subjects (82 bipolar patients and 30 controls) were included. The patients were randomly selected from Punjab Institute of Mental Health (PIMH) and Sheikh Zayed Hospital, Lahore. After the consent of the subjects, venous blood samples were collected. CRP levels were semi-quantitatively estimated by agglutination method. The data obtained was analyzed through SPSS. Results: The difference in the mean CRP level among bipolar and control groups was statistically significant (p = 0.001). Moreover, males had higher CRP levels than females but the difference was non-significant (p=0.134). Comparison of CRP levels among various stages of BD and control showed a significant difference between the groups (p=0.009). Increased CRP levels give an idea about the inflammation and severity of the disease. CRP levels could be of help in the diagnosis and prognosis of BD. Conclusions: The present study suggests a significant association of CRP with bipolar disorder. No significant relation of CRP and gender was depicted. Keywords: Bipolar Disorder, C-reactive protein, Gender